Self-Reported Clinical Practice of Small Animal Cardiopulmonary Resuscitation and Compliance With RECOVER Guidelines Among Veterinarians in Eight Western European Regions - Hagley, Simon P.; Kruppert, Anne; Leal, Rodolfo Oliveira; Pizarro del Valle, José Carlos; Iannucci, Claudia; Hennink, Imke; Boiron, Ludivine; Hoehne, Sabrina N. (Frontiers in Veterinary Science, 2022)
Introduction: The objective of this study was to assess whether small animal veterinarians across Western Europe are compliant with the 2012 cardiopulmonary resuscitation (CPR) guidelines by the Reassessment Campaign on Veterinary Resuscitation (RECOVER). Methods: A previously published online questionnaire from Switzerland was adapted and translated into 7 languages, corresponding to national languages in Austria, France, Germany, Ireland, Italy, Liechtenstein, Netherlands, Portugal, Spain, and the United Kingdom. The survey was distributed via respective national veterinary organizations and social media outlets. A subset of questions was analyzed to evaluate respondent demographics, RECOVER guideline awareness, and to allocate composite compliance scores for CPR preparedness, basic life support (BLS) and advanced life support (ALS). Percentages of group total (95% confidence interval) were calculated. Multivariable logistic regression was used to evaluate the effects of region of practice, gender, age, specialty training, and guideline awareness on compliance. Odds ratios (95% confidence interval) were generated and significance set at P<0.05. Results: Nine-hundred and thirty respondents were included in analysis. Awareness of and compliance with RECOVER guidelines varied widely across regions. Compliance with all assessed RECOVER guideline recommendations was highest in Germany/Austria (14% (7- 27%)) and lowest in France and Portugal (0% (0-3%)). CPR preparedness compliance was higher in participants aware of RECOVER guidelines (OR 10.1 (5.2-19.5)), those practicing in Germany/Austria (OR 4.1 (1.9-8.8)) or UK/Ireland (OR 2.2 (1.3-3.7)), and lower in those practicing in Portugal (OR 0.2 (0.1-0.9)). Specialty training (OR 1.8 (1.1-2.9)), guideline awareness (OR 5.2 (3.2-8.6)), and practice in Germany/Austria (OR 3.1 (1.5-6.5)), UK/Ireland (OR 2.6 (1.7-4.1)), or the Netherlands (OR 5.3 (2.0-14.2)) were associated with increased BLS compliance. ALS compliance was higher in participants with guideline awareness (OR 7.0 (2.9-17.0)), specialty training (OR 6.8 (3.8-12.1)), those practicing in Germany/Austria (OR 3.5 (1.3-9.6)), UK/Ireland (OR 4.0 (1.9-8.3)), or Spain (OR 3.2 (1.2-8.3)) and in younger survey participants (OR 0.9 (0.9-1.0)). Conclusions: Awareness and compliance with RECOVER guidelines varied widely among countries surveyed, however overall compliance scores in all countries were considered low. Further research may highlight factors surrounding poor guideline awareness and compliance so targeted efforts can be made to improve veterinary CPR in Europe.